RESPONSE OF PEANUT PLANT GROWTH AND YIELD TO DECREASED ORGANIC FERTILISER DOSAGE AND INCREASED ORGANIC FERTILISER DOSAGE - Puspitasari, Adelia Eka; Widiwurjani, Widiwurjani; Santoso, Juli (Yayasan Education and Social Center, 2024)
This study used a randomized complete block design (RCB) to evaluate the effect of various doses of organic fertilizer on the growth and yield of peanut plants. This research involved seven treatment units, each with a unique combination of inorganic and organic fertilizers. Each treatment was repeated four times, so there were 28 treatment units. Each unit comprises 16 plants carefully selected and managed to ensure consistent growing conditions. Four plants were taken from each unit as samples for analysis, and 112 sample plants were used to collect growth data and other relevant variables. Peanut cultivation in Indonesia faces serious challenges, such as reduced productivity due to prolonged drought and inadequate agricultural practices. This research aims to determine the impact of lowering the dose of inorganic fertilizer and increasing the use of organic fertilizer on the growth and yield of peanuts. The results showed a significant effect of various fertilizer combinations on growth parameters. Treatment P5 (a combination of inorganic and organic fertilizer) gave the best results in vegetative observations. In contrast, treatment P4 (a combination of inorganic and organic fertilizer) was superior in yield and pod weight. These findings emphasize the importance of implementing integrated fertilizers in peanut cultivation to improve agricultural sustainability. This research provides valuable insights for farmers and researchers in developing more efficient and environmentally friendly farming practices and supporting increased productivity of peanut plants in various environmental conditions